Overview of the development and application of the hyphenated techniques in nutritional analysis - Kotnik, Darja (Acta chimica slovenica, 2011)
The development of some sensitive assays for quantitative nutritional analysis with an emphasis on selected hyphenated analytical techniques is reviewed in the present paper. The majority of work is dedicated to reviewing the development of analytical tools for routine analysis of carbohydrates and lipids in biological samples, many of them introduced in our laboratory. Handling biological matrices, where endogenous compounds can mask the analyte of interest or where the occurrence of the coelution effect of several compounds present in different amounts hinders the analyte's peak integration, is a major challenge. To overcome this challenge, hyphenated techniques have become widespread in laboratory practice. Some of these techniques are reviewed, with special attention given to an effective on-line interface for thin-layer chromatography-mass spectrometry and on-line coupling thin-layer chromatography-gas chromatography. Recently introduced an on-line coupling of ion chromatograph and hybrid RF/DC quadrupole-linear ion trap mass spectrometer represent an analytical tool for the solution of bioanalytical problems. Developed methods using ion chromatography- pulsed amperometric detection and ion chromatography-mass spectrometry techniques for the quantitative evaluation of sugars are presented. This paper represents basic contributions of our research work connected with some of modern hyphenated techniques. However, this review is restricted to the published papers to be significant developments or improvements during the last three decades.
Keywords: analizna kemija; biološki vzorci; carbohydrate and lipid analysis; hrana; hyphenated techniques; ion chromatography-mass spectrometry; kromatografija; masna spektroskopija; thin-layer chromatography-gas chromatography; thin-layer chromatography-mass spectrometry